2019
DOI: 10.1371/journal.pone.0216166
|View full text |Cite
|
Sign up to set email alerts
|

Instruments for the detection of frailty syndrome in older adults: A systematic review

Abstract: Frailty is a dynamic process in which there is a reduction in the physical, psychological and/or social function associated with aging. The aim of this study was to identify instruments for the detection of frailty in older adults, characterizing their components, application scenarios, ability to identify pre-frailty and clinimetric properties evaluated. The study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), under registration number CRD4201703931… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
192
0
32

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(268 citation statements)
references
References 125 publications
2
192
0
32
Order By: Relevance
“…The frailty measure we applied, the CFS, is the most employed frailty instrument in ICUs, and has been validated in a variety of hospital and community health care settings . We have recently reported that the CFS can be used to measure frailty in critical ill patients across the spectrum of health domains, and its performance in ICU patients is comparable with that of comprehensive multidimensional frailty assessment tools .…”
Section: Discussionmentioning
confidence: 99%
“…The frailty measure we applied, the CFS, is the most employed frailty instrument in ICUs, and has been validated in a variety of hospital and community health care settings . We have recently reported that the CFS can be used to measure frailty in critical ill patients across the spectrum of health domains, and its performance in ICU patients is comparable with that of comprehensive multidimensional frailty assessment tools .…”
Section: Discussionmentioning
confidence: 99%
“…Although substantial agreement exists on the theoretical construct of frailty, its clinical implementation is hampered by the lack of an unequivocal operational definition. This impasse is reflected by the existence of numerous instruments for frailty assessment, and each of these identifies only partially overlapping phenotypes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We can define frailty syndrome as a group of health alterations that can affect several aspects, such as the psychological, biological and social aspects, as it is a consequence of a dynamic process that reduces a person’s health status [ 6 ]. Regarding foot conditions in older adult populations, foot disorders and diseases are present most frequently in the frailty population group, comprising approximately 25% [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%